Spectroscopic studies on lipoprotein structure modification under oxidative stress. Issue 3 (2011) - Tache Tache, Andreia Andreia; Litescu Litescu, Simona-Carmen Simona-Carmen; Radu Radu, Gabriel-Lucian Gabriel-Lucian
Abstract : Matrix assisted laser desorption–ionization time of flight (MALDI-ToF) and infrared techniques were used to study oxidative modification of low density lipoproteins (LDL), considered to have the key role in biological process that initiates and accelerates the development of cardiovascular disease. The early identification of lipoperoxidation products creates the opportunity of the efficient prevention of eventual oxidative damages. MALDI analysis of LDL subjected to in vitro oxidation process initiated by 2, 2-azobis(2-amidinopropane) dihydrochloride revealed that some fragments of lipoprotein changed the molecular weight by 16 and 32 Da due to the oxygen or hydroxyl groups attachment, and peroxide or hydroperoxide formation, while Fourier Transformed Infrared studies proved that lipoprotein changes its protein secondary conformation from predominantly α -helix in predominantly β -turn. The increase in free radicals concentration correlated to structural changes, and the presence of transitional metal ion, copper (II), in the oxidation process lead to an enhancing of the damaging effects of free radicals on lipoprotein substrate. It was shown that the toxic effects of oxidants are delayed by the presence of glutathione (10 mM), an endogenous antioxidant.